The Politics of Abortion in New Brunswick - Johnstone, Rachael (Atlantis, 2014)
This paper examines one of the most notorious, yet largely overlooked, provinces in terms of abortion access in Canada: New Brunswick. Through an exploration of the provincial government’s activities and litigation in the province, this article traces the history of abortion regulation in New Brunswick, with particular attention paid to the manner in which social movement activism has shaped policy. It argues for the need to reframe abortion as a matter of equal citizenship. Specifically, it suggests that such a rethinking could generate political pressure for recognition and improved services, and stimulate a public discourse that has the potential to begin breaking down the more complex, extra-legal barriers faced by women in Canada.